Early maladaptive schemes and psychological well-being in patients who attend an outpatient consultation at a Health Service Provider Institution – IPRESS, Lima, 2020 - Monteza Vásquez, Segundo Alamiro (2021)
The objective of this study was to determine the relationship between early maladaptive schemes and the psychological well-being of patients who attend outpatient consultation at a Health Service Provider Institution - IPRESS, Lima, 2020. The research was developed under an approach quantitative, non-experimental design and a correlational scope; In which 120 patients participated (both sexes) who attended the external consulting service of an Institution Provider of Health Services - IPRESS in the city of Lima. Data collection was carried out using two instruments: Young's Scheme Scale (YSQ-SF) and the Bieps-A Psychological Well-being Scale. The study concluded that early maladaptive schemes present a significant (p = 0.000) and inverse (r = -0.764) relationship with psychological well-being in patients who attend an outpatient clinic at an IPRESS, Lima, 2020. That is, the higher In the presence of maladaptive schemes, patients tend to experience lower levels of psychological well-being.